2019
DOI: 10.1039/c8cy02536c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically constructed NiO with improved performance for catalytic transfer hydrogenation of biomass-derived aldehydes

Abstract: A 3D nanometer-scaled NiO material with urchin-like structure was prepared via a facile route, and served as a highly efficient and durable catalyst for catalytic transfer hydrogenation of bio-based furfural to furfuryl alcohol using 2-propanol as H-donor and solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…In the absence of catalyst the only product is 2-(diisopropoxymethyl)furan (DPMF) with a yield of 10 %, which is formed by the acetalization of F with two molecules of 2-propanol. [25,26] This product is also observed over the commercial Al 2 O 3 (DPMF = 5 %), together with a minor amount of FA (7 %). The ability of Al 2 O 3 to catalyse the CTH of F has been recently reported although a large catalyst amount was required to work efficiently.…”
Section: Furfural Conversion Over Hydrotalcite-derived Catalystsmentioning
confidence: 64%
See 1 more Smart Citation
“…In the absence of catalyst the only product is 2-(diisopropoxymethyl)furan (DPMF) with a yield of 10 %, which is formed by the acetalization of F with two molecules of 2-propanol. [25,26] This product is also observed over the commercial Al 2 O 3 (DPMF = 5 %), together with a minor amount of FA (7 %). The ability of Al 2 O 3 to catalyse the CTH of F has been recently reported although a large catalyst amount was required to work efficiently.…”
Section: Furfural Conversion Over Hydrotalcite-derived Catalystsmentioning
confidence: 64%
“…Control experiments with no catalysts or employing commercial γ‐Al 2 O 3 (Sigma‐Aldrich) show a poor conversion of F after 6 h (≤13 %). In the absence of catalyst the only product is 2‐(diisopropoxymethyl)furan (DPMF) with a yield of 10 %, which is formed by the acetalization of F with two molecules of 2‐propanol . This product is also observed over the commercial Al 2 O 3 (DPMF=5 %), together with a minor amount of FA (7 %).…”
Section: Resultsmentioning
confidence: 99%
“…Furfural is accessible from acid-catalyzed tandem hydrolysis-dehydration of hemicellulose or from acid-facilitated transformation of cellulose-derived hexoses [38][39][40], and affords sustainable access to a variety of liquid bio-fuels and valuable chemicals via different upgrading strategies such as, e.g. hydrogenation, oxidation, amination and aldol condensation [41][42][43][44][45]. Amongst the strategies, the reductive amination of furfural with ammonia or primary amines is a versatile and elegant way to synthesize valuable amines, including furfurylamine and its derivatives, which have a large spectrum of applications in the manufacture of pharmaceuticals, pesticides, synthetic resins and useful agrochemicals [46].…”
Section: Reductive Amination Of Furfuralmentioning
confidence: 99%
“…Solid catalysts containing Lewis acids are often used for intermolecular and intramolecular hydrogen transfer, so many researchers use them to catalyze the upgrading reaction of biomass to produce valuable compounds (Li et al, 2014). The use of liquid hydrogen sources (e.g., alcohol and formic acid) instead of high-pressure H 2 addresses the safety hazards posed by hydrogen (He et al, 2019b). In relation to this, it has recently been reported that Lewis acid zeolites, such as Hf- and Zr-, are used for the hydrogenation of biomass-derived carboxides, such as FF and 5-hydroxymethylfurfural, into corresponding alcohols through the reduction of Meerwein-Ponndorf-Verley (MPV), as shown in Table 3.…”
Section: Catalytic Hydrogenation Of Biofuranic Aldehydes To Alcoholsmentioning
confidence: 99%